2022
DOI: 10.1155/2022/4304361
|View full text |Cite
|
Sign up to set email alerts
|

Six Genes Associated with Lymphatic Metastasis in Colon Adenocarcinoma Linked to Prognostic Value and Tumor Immune Cell Infiltration

Abstract: Objective. The aim of the study is to explore the relationship between lymphatic metastasis genes, prognosis, and immune cell infiltration in patients with colon cancer. Methods. Based on the Cancer Genome Atlas Program (TCGA) database, differentially expressed genes and prognostic genes related to colon adenocarcinoma (COAD) lymphatic metastasis were screened and intersected. We used lasso and univariate Cox regression analysis to screen core genes and establish a preliminary prediction model. GO and KEGG enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Further exploration of the GO enrichment analysis revealed that CENPF functions in the cell cycle through regulating mitosis and microtubule binding in various cancers, for instance, CENPF contributes to the deterioration of adrenocortical carcinoma by affecting the cell cycle [ 14 ]. In the heatmap of the GSEA analysis, several ZNFs were upregulated in the CENPF high group, which belong to the zinc finger transcription factor family and have profound impacts on cancer progression [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ], implying a presumable connection between CENPF and these ZNFs. Additionally, CENPI, a constitutive protein of kinetochore, was synergistically upregulated with CENPF (as GSEA results shown), which specifies localization of CENPF to kinetochores and is essential for chromosome segregation and mitosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further exploration of the GO enrichment analysis revealed that CENPF functions in the cell cycle through regulating mitosis and microtubule binding in various cancers, for instance, CENPF contributes to the deterioration of adrenocortical carcinoma by affecting the cell cycle [ 14 ]. In the heatmap of the GSEA analysis, several ZNFs were upregulated in the CENPF high group, which belong to the zinc finger transcription factor family and have profound impacts on cancer progression [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ], implying a presumable connection between CENPF and these ZNFs. Additionally, CENPI, a constitutive protein of kinetochore, was synergistically upregulated with CENPF (as GSEA results shown), which specifies localization of CENPF to kinetochores and is essential for chromosome segregation and mitosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the CRC dataset, ALB, FGG, SERPINC1, AHSG, APOA1, F2, AMBP, APOH, APOB, and KLF20A were the top 10 hub genes in the CRC liver metastasis dataset. ALB is an important transport protein in serum, and decreased ALB expression worsens the prognosis of CRC patients [33] . AHSG is a serum glycoprotein synthesized by hepatocytes and adipocytes that can promote tumor proliferation, migration, and invasion [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated metastasis-associated genes have great potential for cancer prognostic assessment (4)(5)(6)(7)(8). Therefore, this study was conducted to screen the differentially expressed genes (DEGs) of metastatic BC by analyzing the transcriptome data in The Cancer Genome Atlas (TCGA) database, afterwards utilize Cox regression and Lasso regression analysis to identify the independent prognostic factors, and then establish a predictive model.…”
Section: Introductionmentioning
confidence: 99%